An Examination of Transfer of Prisoner Treaty/Agreement: A Benchmark in the Reform of the Criminal Justice System. - Adebayo, M. K. (NIU Journal of Humanities, 2017)
The consensus of opinion in international law is that a state does not have any obligation to surrender an alleged criminal to a foreign state, because one principle of sovereignty is that every state has legal authority over the people within its borders. Such absence of international obligation and the desire for the right to demand such criminals from other countries have caused a web of extradition treaties or agreements to evolve. When no applicable extradition agreement is in place, a sovereign may still request the expulsion or lawful return of an individual pursuant to the requested state’s domestic law. This can be accomplished through the immigration laws of the requested state in some cases or other facets of the requested state’s domestic law. Similarly, the codes of penal procedure in many countries contain provisions allowing for extradition to take place in the absence of an extradition agreement. Sovereign may, therefore, still request the expulsion or lawful return of a fugitive from the territory of a requested state in the absence of an extradition treaty, hence the focus of this paper to elucidate on the rights of prisoners, the transfer of prisoners, an examination of key international transfer of prisoners agreement/treaties/bills, and the procedure for transfer of extradition, and concludes with an advocacy of how transfer/extradition of prisoners can help improve the administration of the criminal justice system particularly in the area of prisoner decongestion, long period of awaiting trial, and the overall welfare of prisoners during the period of incarceration. Keywords: Extradition, Prisoner, Rights, Transfer, Sentence, Administering, State.